Melatonin suppresses sympathetic vasomotor tone through enhancing GABAA receptor activity in the hypothalamus - Yu, Qiyao; Guo, Qi; Jin, Sheng; Gao, Chao; Zheng, Peiru; Li, De-Pei; Wu, Yuming (Frontiers in Physiology, 2023)
Melatonin (5-methoxy-N-acetyl-tryptamine) is a circadian hormone synthesized and secreted by the pineal gland. In addition to regulating circadian rhythms of many physiological functions, melatonin is involved in regulating autonomic nervous function and blood pressure. Hypothalamus paraventricular nucleus (PVN), receiving melatonin projections from the superchiasmatic nucleus, is a critical brain region to regulate neuroendocrine and cardiovascular function. Here, we determined the synaptic mechanisms involved in the effect of melatonin on the sympathetic outflow and blood pressure. Microinjection of melatonin into the PVN produced a depressor effect and decreased renal sympathetic nerve activity (RSNA). While microinjection of luzindole, a non-selective melatonin receptor antagonist, into the PVN did not change melatonin-induced sympathoinhibition, GABAA receptor antagonist bicuculline eliminated melatonin-induced sympathoinhibition. Furthermore, melatonin decreased firing rate of retrogradely labeled PVN neurons which project to the rostroventrolateral medulla (RVLM), an effect was not altered by luzindole but eliminated by bicuculline. Melatonin significantly increased the amplitude of spontaneous and evoked GABAergic inhibitory synaptic currents, as well as GABA-induced currents. These data suggest that melatonin in the PVN suppresses sympathetic vasomotor tone through enhancing GABAA receptor activity. This study provides novel information for understanding the cellular mechanisms involved in the effect of melatonin on regulating blood pressure and sympathetic output.